2015
DOI: 10.1289/ehp.1307865
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Blood Manganese and Early Neurodevelopment: The Mothers and Children’s Environmental Health (MOCEH) Study

Abstract: BackgroundManganese is an essential trace element and common component of water, soil, and air. Prenatal manganese exposure may affect fetal and infantile neurodevelopment, but reports on in utero manganese exposure and infant neurodevelopment are rare.ObjectiveThis study was conducted to investigate a relationship between maternal blood manganese level and neurodevelopment of infants at 6 months of age.MethodsData were obtained from the Mothers and Children’s Environmental Health (MOCEH) birth cohort study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
87
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 34 publications
5
87
3
Order By: Relevance
“…We identified 14 studies that examined the association between Mn and neurodevelopmental or cognitive outcomes in neonates or children (Supplement 2) [5568]. Most studies were cross-sectional (n=10), and four were prospective cohorts.…”
Section: Epidemiologic Evidence For Neurotoxic Effects Of Manganesementioning
confidence: 99%
See 4 more Smart Citations
“…We identified 14 studies that examined the association between Mn and neurodevelopmental or cognitive outcomes in neonates or children (Supplement 2) [5568]. Most studies were cross-sectional (n=10), and four were prospective cohorts.…”
Section: Epidemiologic Evidence For Neurotoxic Effects Of Manganesementioning
confidence: 99%
“…All four of the prospective studies reviewed support the notion that the prenatal and early postnatal period may be a sensitive developmental window for Mn exposure with regards to neurodevelopment [58, 61, 67, 68]. In a large prospective cohort study of neonates from China, a cord serum Mn threshold of 5 μg/L was identified, above which three-day-olds showed cognitive deficits as measured by the Neonatal Behavioral Neurological Assessment (NBNA) [67].…”
Section: Epidemiologic Evidence For Neurotoxic Effects Of Manganesementioning
confidence: 99%
See 3 more Smart Citations